PENINGKATAN KONSEP KEAGAMAAN SISWA MELALUI INTEGRASI PAI DENGAN KEGIATAN ROHIS DI SEKOLAH - Rahmat Fadli; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The lack of existence of ROHIS activities in the scope of students makes the integration of Islamic Religious Education subjects with Spiritual activities also fade. So that Islamic religious education is not able to apply fully optimally and efficiently in teaching and learning activities. Therefore, to see what if the rohis rise again and become friends for Islamic religious education in educating religious concepts in each student will they be able to get optimal and efficient PAI learning? The following article uses descriptive qualitative research with library research as a data collection tool in this study. So thus, this study concludes that the integration between PAI and ROHIS has a great importance in shaping the character of students who have religious character. This can help students in strengthening religious and moral values that are applied in everyday life. However, keep in mind that this integration must be carried out in a precise and measurable manner to avoid imbalances or even misunderstandings among students. Therefore, the integration between PAI and ROHIS must be carried out by paying attention to differences and respecting the values of tolerance